PPARγ and Its Agonists in Chronic Kidney Disease - Yuhua Ma; Manman Shi; Yuxin Wang; Jian Liu (International Journal of Nephrology)
Chronic kidney disease (CKD) has become a global healthcare issue. CKD can progress to irreversible end-stage renal diseases (ESRD) or renal failure. The major risk factors for CKD include obesity, diabetes, and cardiovascular diseases. Understanding the key process involved in the disease development may lead to novel interventive strategies, which is currently lagging behind. Peroxisome proliferator-activated receptor γ (PPARγ) is one of the ligand-activated transcription factor superfamily members and is globally expressed in human tissues. Its agonists such as thiazolidinediones (TZDs) have been applied as effective antidiabetic drugs as they control insulin sensitivity in multiple metabolic tissues. Besides, TZDs exert protective effects in multiple other CKD risk disease contexts. As PPARγ is abundantly expressed in major kidney cells, its physiological roles in those cells have been studied in both cell and animal models. The function of PPARγ in the kidney ranges from energy metabolism, cell proliferation to inflammatory suppression, although major renal side effects of existing agonists (including TZDs) have been reported, which limited their application in treating CKD. In the current review, we systemically assess the function of PPARγ in CKDs and the benefits and current limitations of its agonists in the clinical applications.